2017
DOI: 10.1111/1467-9566.12520
|View full text |Cite
|
Sign up to set email alerts
|

Social class, dementia and the fourth age

Abstract: Research addressing social class and dementia has largely focused on measures of socioeconomic status as causal risk factors for dementia and in observed differences in diagnosis, treatment and care. This large body of work has produced important insights but also contains numerous problems and weaknesses. Research needs to take account of the ways in which ageing and social class have been transformed in tandem with the economic, social and cultural coordinates of late modernity. These changes have particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 114 publications
(150 reference statements)
0
19
1
Order By: Relevance
“…While other studies emphasise the determining influence of socio‐economic status, this study is too small to draw conclusions of this type. It can, however, form the basis for more extensive future research.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…While other studies emphasise the determining influence of socio‐economic status, this study is too small to draw conclusions of this type. It can, however, form the basis for more extensive future research.…”
Section: Discussionmentioning
confidence: 75%
“…The consistent message of public health and epidemiological research is that social disadvantage and dementia are interconnected: with those suffering social disadvantage being more at risk of developing dementia in later life. These studies present the relationship between social disadvantage, exclusion and dementia in a certain way, however: situating social location as the preeminent factor in how dementia is understood and experienced . They do not therefore address the possibility that social identity may be directly impacted by dementia or that unique forms of disadvantage and exclusion arise because of the condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between dementia and social status is prominent . Studies suggested that socioeconomic position and being working class are major risk factors for developing dementia . Other probable factors for dementia are inconsistency in diagnosis, access to treatment and care, and personal perceptions of disease .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the ways in which dementia is conceptualised may also be shaped by social location. Although work on social class and dementia tends to be restricted to differences in associated risk factors for developing the condition or different levels of access to diagnosis, care, and support, there is a growing recognition that social class identities have a significant role to play in the ways in which dementia is both experienced and conceptualised [10]. …”
mentioning
confidence: 99%